A Corpus Approach to Ecological Discourse Analysis and L2 Writing Pedagogy (2015) - Tamucc, Mara Barbosa (Ecolinguística: Revista brasileira de ecologia e linguagem (ECO-REBEL), 2016)
POOLE, Robert. A Corpus Approach to Ecological Discourse Analysis and L2 Writing Pedagogy. Tese de doutorado, Universidade do Arizona (EUA), 2015.